Partisipasi Aktif Masyarakat Dalam Proses Pemilihan Kepala Kampung Salor Indah - moento, paul adryani (SOCIETAS, 2024)
The research aims to determine the Political Participation of the Community in the Election of the Head of Kampung Salor Indah in Merauke Regency. To obtain research data, the researcher interviewed several people as informants. Data analysis used the descriptive method. This research used a qualitative approach, while the data analysis technique used three stages: data reduction, data presentation, and conclusion drawing. The results of this article are that the community's participation in the election of the head of the village in Kampung Salor Indah in 2021 experienced a significant increase. This was due to the active role of the community in socializing the importance of participating in political activities. In the political discussions organized by the Village Head Election Committee, the committee provided socialization about the importance of using the right to vote and strategies to influence the community to participate in political activities. The candidate for the head of the village successfully gained support from the community through effective and polite campaigning. Additionally, the community participated in farmer and people's business groups that had a significant influence on local politics. This article emphasizes the importance of community participation in political activities and the role of community groups in determining the selected candidates.